The Journal of Law and Religion - Second Life - Failinger, Marie A. (Journal of law and religion, 2025)
After its initial founding by the Council on Religion and Law at Harvard, the Journal of Law and Religion had its first life at Hamline University School of Law beginning in 1983. This essay is a history of its second life - from 1987/1988 to 2013 - describing the vision and the people who pursued that vision through the journal in those years and some of the roundtables and symposia it published.